Introduction to Chinese Culture Cultural History, Arts, Festivals and Rituals (Springer Singapore, 2018)
Promoting cultural understanding in a globalized world, this text is a key tool for students interested in understanding the fundamentals of Chinese culture. Written by a team of experts in their fields, it offers a comprehensive and detailed introduction to Chinese culture and addresses the fundamentals of Chinese cultural and social development. It notably considers Chinese traditional culture, medicine, arts and crafts, folk customs, rituals and etiquette, and is a key read for scholars and students in Chinese Culture, History and Language.